2002
DOI: 10.1159/000067288
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Foods Traditionally Regarded as &lsquo;Heating&rsquo; and &lsquo;Cooling&rsquo; on Prostaglandin E<sub>2</sub> Production by a Macrophage Cell Line

Abstract: Some components of natural foods may enhance or inhibit prostaglandin formation and potentially affect the inflammation condition. A macrophage cell line, RAW264.7, was employed to examine the effects of foods traditionally regarded as ‘heating’ or ‘cooling’ on the production of PGE2, a well-known proinflammatory mediator. Foods traditionally regarded as ‘heating’ (litchi, longan, and dried longan) or ‘cooling’ (chrysanthemum flower, bitter gourd, and lotus seed plumule) were extracted sequentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…The 100g edible portion of litchi contains water (81.76 g), protein (0.83 g), lipids (0.44 g), ash (0.44 g), carbohydrates (16.53 g), fiber (1.3g) and sugars (15.23 g) (Table 1). Both in-vitro and in-vivo studies have been conducted exploring the beneficial effects of Litchi, most of which suggest a solid potential for the use of Litchi extract as a supplemental therapeutic to ameliorate diabetes, obesity and its complications (Huang & Wu, 2002; Guo et al, 2004; Obrosova et al, 2010). …”
Section: Exotic Fruits and Their Biodefensive Potential In Metabolmentioning
confidence: 99%
See 1 more Smart Citation
“…The 100g edible portion of litchi contains water (81.76 g), protein (0.83 g), lipids (0.44 g), ash (0.44 g), carbohydrates (16.53 g), fiber (1.3g) and sugars (15.23 g) (Table 1). Both in-vitro and in-vivo studies have been conducted exploring the beneficial effects of Litchi, most of which suggest a solid potential for the use of Litchi extract as a supplemental therapeutic to ameliorate diabetes, obesity and its complications (Huang & Wu, 2002; Guo et al, 2004; Obrosova et al, 2010). …”
Section: Exotic Fruits and Their Biodefensive Potential In Metabolmentioning
confidence: 99%
“…These findings suggest that the Litchi fruit possesses bioactive components that enhance body’s immune system, which can protect from diabetes or obesity induced chronic inflammation. It was further explored that Litchi extract enhances basal prostaglandin E2 (PGE2) production in a macrophage cell line (RAW264.7), which is considered a key inhibitor of the inflammatory immune response (Huang & Wu, 2002). …”
Section: Exotic Fruits and Their Biodefensive Potential In Metabolmentioning
confidence: 99%
“…Wang and coworkers showed that Litchi pericarp ethanol extract inhibited the in vitro and in vivo growth of mouse hepatocellular carcinoma and both estrogen-dependent and independent human breast carcinoma cells [10, 11]. However, the Litchi pericarp is the edible part of the Litchi fruit, and overdosing may lead to some consumers' uncomfortable “heating” [12]. In recent reports, polyphenol compounds from Litchi seeds were identified and composed of a variety of proanthocyanidins and flavonoid glycoside [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…The aerial part of A. paniculata is commonly used in Chinese medicine. According to Chinese medicine theory, A. paniculata 'cools' and relieves internal heat, inflammation and pain and is used for detoxication [4-6]. …”
Section: Introductionmentioning
confidence: 99%